Spatial analysis of Prosopis Juliflora trees, its environmental and developmental effects on Wadi Yiba in the southwest of Saudi Arabia - Alshehri, Norah Ali (Journal of natural sciences, life and applied sciences, 2021)
Prosopis Juliflora is an invasive shrub or tree native to South American countries. It is one of the most important exotic and invasive organisms that are spread in the Kingdom of Saudi Arabia. This study concentrates on investigating the widespread of Prosopis Juliflora  in Wadi Yiba، located in the southwest of the Kingdom، and given the possibilities offered by geographic information system (GIS) and remote sensing to help determine the areas of spread of the plant and its size، and to take the best capabilities، especially with regard to processing and analyzing large and diverse spatial information، the present research aims to use this in evaluating the current and future situation of the spread of plants in Wadi Yiba، and the extent of its impact on the environment، while suggesting appropriate ways to manage it. The research relied on the use of Landsat images، working with the subtraction method، and subjecting the images to the object-oriented classification، by taking 30 specimens for each cover and merging these specimens، and the layers of vegetation cover were derived using the normalized difference vegetation index (NDVI) for each year. The research concluded that there is a concentration in the spread of Prosopis Juliflora in the center and north of Wadi Yiba، especially in the city of Therban and villages of Al-Balqa’a، Al-Tala’i، Sabt Al-Jara، and Khamis Harb، with a spread along the valley to the estuary. At the end، the research recommended the establishment of a research center for the study of Prosopis Juliflora in Assir region، and an attempt to develop economic plans to benefit from Prosopis Juliflora in Wadi Yiba.
Keywords: Persops; Wadi Yebah; vegetation cover; environment; invasive plant